2016
DOI: 10.1259/dmfr.20150254
|View full text |Cite
|
Sign up to set email alerts
|

Dose optimization by altering the operating potential and tube current exposure time product in dental cone beam CT: a systematic review

Abstract: Objectives: Current guidelines highlight the need to optimize exposure parameters on CBCT equipment to levels that are as low as diagnostically acceptable. This systematic review aimed to answer the question "Can altering operating potential (kV) and tube current exposure time product (mAs) on CBCT machines reduce radiation dose to patients undergoing dental and/ or maxillofacial scans without a detrimental impact on image quality/diagnostic accuracy?" Methods: Studies were selected and results reported follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…These results support the proposal that by reducing tube current, it is possible to reduce radiation dosage without image quality degradation for implant planning. These results are in agreement with those of previous studies 21314. However, reducing the tube current deteriorated the image quality for periapical diagnosis.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results support the proposal that by reducing tube current, it is possible to reduce radiation dosage without image quality degradation for implant planning. These results are in agreement with those of previous studies 21314. However, reducing the tube current deteriorated the image quality for periapical diagnosis.…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have been conducted on CBCT image quality, but insufficient information has been published on the assessment of the relationship between image quality and the visibility of anatomic structures corresponding to specific diagnostic tasks 2. Only 3 studies have evaluated 2 or more diagnostic tasks 3911.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In light of the concerns about radiation dose from CBCT imaging, dose optimization studies have been reported, with a couple of recent review articles summarizing previous studies nicely (Goulston, Davies, Horner, & Murphy, ; McGuigan, Duncan, & Horner, ). In a systematic review, the need for consistent test objects, methodologies, and reporting of techniques was identified for better comparison between studies; despite these shortcomings, the authors concluded that CBCT dose reduction should be possible without compromising the diagnostic quality, at least for some imaging tasks (Goulston et al, ). McGuigan et al () concluded that optimization of kV and mA is challenging to balance the image quality with radiation dose and noted a need to relate the objective metrics of image quality to clinical tasks and radiation dose.…”
Section: Introductionmentioning
confidence: 99%